Measurements of $$π ^± $$ π± , K$$^± $$ ± , p and $${\bar{\text {p}}}$$ p¯ spectra in proton-proton interactions at 20, 31, 40, 80 and 158 $$\text{ GeV }/c$$ GeV/c with the NA61/SHINE spectrometer at the CERN SPS - A. Aduszkiewicz (European Physical Journal C: Particles and Fields, 2017)
Abstract Measurements of inclusive spectra and mean multiplicities of $$π ^± $$ π± , K$$^± $$ ± , p and $${\bar{\text {p}}}$$ p¯ produced in inelastic p + p interactions at incident projectile momenta of 20, 31, 40, 80 and 158 $$\text{ GeV }/c$$ GeV/c ($$\sqrt{s} = $$ s= 6.3, 7.7, 8.8, 12.3 and 17.3 $$\text{ GeV }$$ GeV , respectively) were performed at the CERN Super Proton Synchrotron using the large acceptance NA61/SHINE hadron spectrometer. Spectra are presented as function of rapidity and transverse momentum and are compared to predictions of current models. The measurements serve as the baseline in the NA61/SHINE study of the properties of the onset of deconfinement and search for the critical point of strongly interacting matter.